Factors influencing work-life balance among Petronas employees / Muhamad Amir Zaqwan Mohd Ali - Mohd Ali, Muhamad Amir Zaqwan (Faculty of Business and Management, 2018)
This study examines on the factors influencing work-life balance among employees of Petrolaim Nasional Berhad (PETRONAS). Work-life balance is a broad scope that encompasses many determinants but the researcher specifically focuses on four determinants that are time-off from work, allegiance to work, flexibility on work schedule, and workplace support. Data were collected from 100 respondents using convenience sampling. The data collected was then evaluated by using Statistical Package for the Social Science (SPSS) Version 23 Software. Using SPSS, numerous tests were converged such as reliability analysis, descriptive analysis Pearson’s correlation and multiple regression analysis. The result indicated that that there is positive significant relationship between time-off from work and workplace support with wok-life balance. However, flexibility on work schedule and allegiance to work recorded an insignificant relationship with work-life balance. Recommendation and direction for future studies were discussed in this study.